Severe multiple trauma: Pulmonary lobe burst - Piacenza, Guillermo; Castiglioni, Juan C.; Bergalli, Luis; Perrier, José P.; Torterolo, Edgardo; Viola, Humberto (Cirugía del Uruguay, 1979)
The paper describes the case of a patient sufering from serious abdominal and thoracic Jesions. Interpretation of diagnosis is made taking into consideration primary lesiona! balance and initial response to revival treatment. There follows a description of surgical conduct and of there to changes there to according to response obtained. Finally the importance of adopting a dynamic criteria based on permanent control of the patient's evolution, is discussed.